Issues in onfarm experimentation at Gandajika, Zaire - Shannon, D.A.; Kubeng, M.; Mpoy, M.C. (1991)
Farming systems research (FSR) at Gandajika, Zaire, is conducted by the national Legume Program (Programme National Legumineuses-PNL), which is part of the Applied Research and Extension Project (Projet de Recherche Agronomique Appliquee et Vulgarisation-RAV) of the department of Agriculture of Zaïre. RAV has a mandate for crop improvement. FSR and extension in cassava, maize and four grain legume crops.